Effect of attainment value and positive thinking as moderators of employee engagement and innovative work behaviour - Peerapong Pukkeeree; Khahan Na-Nan; Natthaya Wongsuwan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Influences of attainment value and positive thinking were assessed as moderators of employee engagement and innovative work behaviour. A cross-sectional design was utilised with questionnaires submitted to 348 human resource officers to test the proposed relationships. SPSS 21 and PROCESS macro 3.1 were used for statistical analysis. Results revealed that positive thinking effectively moderated attainment value and employee engagement with regard to innovative work behaviour with statistical significance. Results can be utilised by managers and human resource departments to promote and support innovative work behaviour. Moreover, employees should be encouraged and motivated to perceive attainment value through positive thinking. Findings contribute to the literature on employee engagement and innovative work behaviour by highlighting that attainment value and positive thinking act as moderators that promote employee engagement and innovative work behaviour.
Keywords: 650; attainment value; employee engagement; innovative work behaviour; positive thinking